The Influence of Work Discipline, Awarness, Work Environment on Employee Perfromance at PT Samara Hutama Innovation - Diotama, Nanda (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a quantitative study using a questionnaire addressed to employees of PT. Samara Inovasi Hutama. Sampling in this study was carried out by distributing questionnaires with a total sample of 40 respondents. The design used in this study is hypothesis testing using the SmartPLS 4.0 statistical tool.The results of this study provide an explanation that the variable Awareness has a positive effect on the performance of employees of PT. Samara Inovasi Hutama. However, the variables of work discipline and work environment have no effect on the performance of employees of PT. Samara Inovasi Hutama in this study indicating that work discipline and work environment are not the main considerations in employee performance.